The value of pre-discharge occupational therapy home visits for patients who have had a stroke: p erceptions of patients, occupational therapists and experts - Fellows, Karen Rachael (2014)
Pre-discharge occupational therapy home visits after stroke are routinely conducted during the discharge planning process. However, there is limited research evidence about the value of these visits for patients.